2019
DOI: 10.1038/s41467-019-12537-3
|View full text |Cite
|
Sign up to set email alerts
|

Direct imaging of light-element impurities in graphene reveals triple-coordinated oxygen

Abstract: Along with hydrogen, carbon, nitrogen and oxygen are the arguably most important elements for organic chemistry. Due to their rich variety of possible bonding configurations, they can form a staggering number of compounds. Here, we present a detailed analysis of nitrogen and oxygen bonding configurations in a defective carbon (graphene) lattice. Using aberration-corrected scanning transmission electron microscopy and single-atom electron energy loss spectroscopy, we directly imaged oxygen atoms in graphene oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 37 publications
4
35
0
Order By: Relevance
“…For instance, researchers have directly observed nitrogen and oxygen atoms in N-doped graphene lattice and graphene oxide, respectively, along with their chemical forms via atomic resolution imaging (Figure 3c,d). [99] (Surprisingly, oxygen bound with three carbon atoms was also visualized, which had been rarely www.advancedsciencenews.com www.advmatinterfaces.de…”
Section: Analytical Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, researchers have directly observed nitrogen and oxygen atoms in N-doped graphene lattice and graphene oxide, respectively, along with their chemical forms via atomic resolution imaging (Figure 3c,d). [99] (Surprisingly, oxygen bound with three carbon atoms was also visualized, which had been rarely www.advancedsciencenews.com www.advmatinterfaces.de…”
Section: Analytical Approachesmentioning
confidence: 99%
“…[64] Recently, Hofer et al demonstrated nitrogen doping by irradiating nitrogen ions onto graphene on a TEM grid, and atomic resolution imaging confirmed that the doped nitrogen prefers to bind with three carbon atoms (graphitic form). [99] Based on these observations from different research groups, high-quality tunable nitrogen doping of graphene is possible; and particular bonding configurations, a large continuous area, and single-layer thickness can be achieved by controlling the synthesis parameters such as, the growth temperature, growth duration, precursor sublimation temperature (for solid precursors only), and even by laser deposition and ion implantation methods.…”
Section: N-doped Graphenementioning
confidence: 99%
“…1B, Yao and co-workers observed structural defects with different combinations (e.g., pentagons, heptagons and octagons), which mainly dominated on the hole-edge defects, while the regular hexagonal graphene structure dominated the main region of the carbon material [34]. Recently, Hofer and co-workers proposed an AC-TEM method for the direct visualization of triple-coordinated oxygen in graphene [140]. In addition, other kinds of defects, such as oxygen defects, have also been visualized by AC-TEM [141][142][143].…”
Section: Transmission Electron Microscopymentioning
confidence: 99%
“…31 The formation of triplecoordinated oxygen should not surprise as this configuration was already proven to exist both theoretically and experimentally in graphene. 41,42 When there are two initial zig-zag lines of oxygens, the resulting pore area is minimal (Fig. 3c), although in some cases, very small holes appear as in Panel II of Fig.…”
Section: Physical Chemistry Chemical Physics Accepted Manuscriptmentioning
confidence: 99%